Hazarat Yousaf (AS) - Karam , Ambia
Prophet Yusuf (AS) remained calm and resigned to the Will of Allah, despite being abandoned in the well by his brothers. He also bore the shame of being sold as a slave patiently. He also accepted his false imprisonment. In return for his forbearance, Allah raised his position till it was the highest in Egypt.